RETRACTED: Statistical analysis of the development levels of students’ endurance qualite based on student’s mathematical-statistical criteria - Nurullaev Аbduhamid; Ibragimov Аlisher; Еlkulieva Feruza; Nurullayev Abdurashid (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001